2007
DOI: 10.1159/000107284
|View full text |Cite
|
Sign up to set email alerts
|

Acute Morphine Administration Reduces White Blood Cells’ Capability to Induce Innate Resistance against HSV-1 Infection in BALB/c Mice

Abstract: Objective: It has been reported that acute morphine administration modulates innate immune response to herpes simplex virus 1 (HSV-1) infection. In this study, the effect of acute morphine on innate resistance and its probable mechanisms in increasing the mortality rate during HSV-1 infection were investigated. Methods: Mice were infected with HSV-1 24 h prior to different doses of morphine or saline administration and the mortality rate was recorded. Spleen cells were obtained from morphine- or saline-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Opioids administration is known to affect the course of HSV infection because of their immunosuppressive function. For example, morphine, a broadly studied and widely used opioid, is known to alter HSV infection, immune response, as well as latency (Jamali et al, 2007a , 2012 ; Mojadadi et al, 2009 ; Bauchat, 2010 ).…”
Section: Opioids and Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids administration is known to affect the course of HSV infection because of their immunosuppressive function. For example, morphine, a broadly studied and widely used opioid, is known to alter HSV infection, immune response, as well as latency (Jamali et al, 2007a , 2012 ; Mojadadi et al, 2009 ; Bauchat, 2010 ).…”
Section: Opioids and Viral Infectionmentioning
confidence: 99%
“…It has been clearly demonstrated that morphine alters innate immune responses, which affect the ability of an infected host to mount a specific immune response and clear HSV-1 (Sheridan and Moynihan, 2005 ). Acute morphine administration diminishes the ability of white blood cells to induce a protective innate immune defense against HSV-1 infection through inhibition of IFN-γ production and NK cell activity (Jamali et al, 2007a ). Mojadadi et al found that acute morphine administration significantly reduced cytolytic T lymphocyte response, lymphocyte proliferation, and IFN-γ production, which consequently reactivated HSV-1 latency in BALB/c mice (Mojadadi et al, 2009 ).…”
Section: Opioids and Viral Infectionmentioning
confidence: 99%
“…In general, opioids mediate immunosuppression although their actions are complicated, often indirect and not well understood. Nonetheless, acute and chronic opioid administration is known to have inhibitory effects on humoral and cellular immune responses including antibody production, natural killer cell activity, cytokine expression, and phagocytic activity [235, 236, 238240]. In vivo and in vitro studies indicated that opioid receptor stimulation exerts suppression of multiple components of the immune defense response including natural killer (NK) cell activity [241], neutrophil complement and immunoglobulin receptor expression [242], chemokine-induced chemotaxis [243] and phagocytosis [244].…”
Section: Advances In Research On Opioid Receptor Functionsmentioning
confidence: 99%
“…Treatment of normal human astrocytes with morphine leads to significant down-regulation of gene expression for β-chemokines, MCP-1, and MIP-1β, while reciprocal up-regulation of the expression of their specific receptors, CCR2b, CCR3, and CCR5, respectively, and reversed by naloxone [247]. In addition, acute administration of morphine significantly decreased NK cell cytotoxicity and interferon-gamma mRNA levels, and increased the mortality rate of mice infected with herpes simplex virus 1 [240]. DOR agonist, DPDPE, triggers monocyte adhesion [248].…”
Section: Advances In Research On Opioid Receptor Functionsmentioning
confidence: 99%
“…Our previous work has shown that acute morphine administration increases mortality during HSV-1 infection in BALB/c mice (7). In humans, morphine administration induces reactivation of latent herpes simplex labialis (8).…”
Section: Introductionmentioning
confidence: 97%